BcXYG1, a Secreted Xyloglucanase from Botrytis cinerea, Triggers Both Cell Death and Plant Immune Responses. Issue 1 (14th July 2017) - Zhu, Wenjun; Ronen, Mordechi; Gur, Yonatan; Minz-Dub, Anna; Masrati, Gal; Ben-Tal, Nir; Savidor, Alon; Sharon, Itai; Eizner, Elad; Valerius, Oliver; Braus, Gerhard H.; Bowler, Kyle; et al.
Abstract : A cell death-inducing apoplastic protein facilitates necrosis and establishment of the pathogen Botrytis cinerea but also is recognized by the plant immune system and triggers a defense response. Abstract: In search of Botrytis cinerea cell death-inducing proteins, we found a xyloglucanase (BcXYG1) that induced strong necrosis and a resistance response in dicot plants. Expression of the BcXYG1 gene was strongly induced during the first 12 h post inoculation, and analysis of disease dynamics using PathTrack showed that a B. cinerea strain overexpressing BcXYG1 produced early local necrosis, supporting a role of BcXYG1 as an early cell death-inducing factor. The xyloglucanase activity of BcXYG1 was not necessary for the induction of necrosis and plant resistance, as a mutant of BcXYG1 lacking the xyloglucanase enzymatic activity retained both functions. Residues in two exposed loops on the surface of BcXYG1 were found to be necessary for the induction of cell death but not to induce plant resistance. Further analyses showed that BcXYG1 is apoplastic and possibly interacts with the proteins of the plant cell membrane and also that the BcXYG1 cell death-promoting signal is mediated by the leucine-rich repeat receptor-like kinases BAK1 and SOBIR1. Our findings support the role of cell death-inducing proteins in establishing the infection of necrotrophic pathogens and highlight the recognition of fungal apoplastic proteins by the plant immune system as an important mechanism of resistance against this class of pathogens.